EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KELAPA SAWIT DI KECAMATAN MARABAHAN KABUPATEN BARITO KUALA - Arisanty, Deasy; Syarifuddin1, Syarifuddin1 (Universitas Negeri Semarang, 2017)
Barito Kuala District experienced a land use change from swamp forests and rice fields to palm oil fields. This study aims to evaluate the land suitability for oil palm plantation in Marabahan sub-district, Barito Kuala District. Samples were obtained on each map of the land unit. The number of land units is 32 units of land. Land unit map is obtained from overlay landform, land use, land, and slope map. Data were analyzed by matching method. The land suitability class for oil palm plantations is somewhat suitable (S3) with a drainage and unconditionally constrained (N1) boundary with drainage barrier. The area with a suitable land suitability (S3) is 138.7 km2. The area of land suitability of unconditional land (N1) is 91.0 km2. Drainage becomes a barrier because the research area is a swamp area that is always inundated, especially for peat antiklinal basin land form.